The Association between ABO and Rh Blood Groups and Risk of Endometriosis in Iranian Women - Farideh Malekzadeh (International Journal of Fertility and Sterility, 2018)
Background Endometriosis is a common gynaecological disease that affects quality of life for women. Several studies have revealed that both environmental and genetic factors contribute to the development of endometriosis. The aim of this study was to investigate the distribution of ABO and Rh blood groups in Iranian women with endometriosis who presented to two referral infertility centers in Tehran, Iran. Materials and Methods In this case-control study, women who referred to Royan Institute and Arash Women’s Hospital for diagnostic laparoscopy between 2013 and 2014 were assessed. Based on the laparoscopy findings, we categorized the women into two groups: endometriosis and control (women without endometriosis and normal pelvis). Chi-square and logistic regression tests were used for data analysis. Results In this study, we assessed 433 women, of which 213 patients were assigned to the endometriosis group while the remaining 220 subjects comprised the control group. The most frequent ABO blood group was O (40.6%). The least frequent blood group was AB (4.8%). In terms of Rh blood group, Rh+ (90.1%) was more frequent than Rh- (9.9%). There was no significant correlation between ABO (P=0.091) and Rh (P=0.55) blood groups and risk of endometriosis. Also, there was no significant difference between the two groups with regards to the stage of endometriosis and distribution of ABO and Rh blood groups (P > 0.05). Conclusion Although the O blood group was less dominant in Iranian women with endometriosis, we observed no significant correlation between the risk of endometriosis and the ABO and Rh blood groups. Endometriosis severity was not correlated to any of these blood groups.